2020
DOI: 10.1096/fj.201901880r
|View full text |Cite
|
Sign up to set email alerts
|

Lifespan‐extending interventions enhance lipid‐supported mitochondrial respiration in Caenorhabditis elegans

Abstract: Dietary restriction and reduced reproduction have been linked to long lifespans in the vast majority of species tested. Although decreased mitochondrial mass and/or function are hallmarks of aging, little is known about the mechanisms by which these organelles contribute to physiological aging or to the effects of lifespan-extending interventions, particularly with respect to oxidative phosphorylation and energy production. Here, we employed the nematode Caenorhabditis elegans to examine the effects of inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
2
6
0
Order By: Relevance
“…The ability of DR to preserve Δψ m during early aging does not appear to involve the activity of UCPs, but instead requires both mitochondrial ANT and IF1 activity. We also find that fatty acid metabolism is required for preservation of Δψ m by DR, consistent with a recent report in worms that fatty acid metabolism promotes longevity [21], as well as numerous studies in mammals showing that DR increases fatty acid oxidation [36, 47-49]. While it remains difficult to quantify or control Δψ m in vivo in mammals, this work should serve to orient future experiments to define mechanisms underlying these observations in worms and other systems.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The ability of DR to preserve Δψ m during early aging does not appear to involve the activity of UCPs, but instead requires both mitochondrial ANT and IF1 activity. We also find that fatty acid metabolism is required for preservation of Δψ m by DR, consistent with a recent report in worms that fatty acid metabolism promotes longevity [21], as well as numerous studies in mammals showing that DR increases fatty acid oxidation [36, 47-49]. While it remains difficult to quantify or control Δψ m in vivo in mammals, this work should serve to orient future experiments to define mechanisms underlying these observations in worms and other systems.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore we tested the hypothesis that fatty acid oxidation is what fuels preservation of Δψ m by DR by directly inhibiting fat oxidation with the drug perhexiline [20]. Prior work has shown that perhexiline prevents lifespan extension from DR [21], and we found that perhexiline prevented preservation of Δψ m in response to DR and, instead, significantly reduced it (Figure 1D). Perhexiline also significantly reduced Δψ m compared to fed control animals, suggesting fatty acid oxidation supports baseline in vivo Δψ m .…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations